2001
DOI: 10.2134/jeq2001.3041195x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Continuous‐Flow Sequential Extraction Procedure for Metal Speciation in Solids

Abstract: A continuous-flow extraction system was developed to speed up, facilitate, and improve the accuracy of the chemical fractionation of metals in solid materials. A three-step sequential extraction scheme was used to evaluate the novel system by analyzing calcium (Ca), iron (Fe), manganese (Mn), copper (Cu), and zinc (Zn) in a soil certified reference material (National Institute of Standards and Technology [NIST] SRM 2710). In the proposed system, extraction occurred in a closed chamber through which extractants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 27 publications
2
57
0
4
Order By: Relevance
“…Tem-se verificado que os elementos de maior mobilidade encontram-se, predominantemente, nas formas químicas solúvel, trocável e ligados a carbonato, enquanto os de baixa mobilidade aparecem ligados às frações óxidos de Fe, Mn, além das frações orgânica e residual (Amaral Sobrinho et al, 1994). Apesar das vantagens do processo de extrações sequenciais em relação apenas à determinação dos teores totais de metais pesados no solo, podem ocorrer problemas de baixa seletividade dos extratores (Shan & Chen, 1993;Shiowatana et al, 2001), redistribuição dos metais durante os processos de extração (Tu et al, 1994;Rakasasalaya et al, 1996) e dependência dos resultados das condições operacionais (Sahuquillo et al, 1999 ao ar e passadas em peneira com malha de 2 mm (TFSA). A textura e as características químicas da TFSA (métodos descritos em Embrapa, 1997;Kummer et al, 2010) e a mineralogia da fração argila (métodos apresentados por Melo et al, 2001Melo et al, , 2002Kummer et al, 2010) das amostras são apresentadas nos quadros 2 e 3, respectivamente.…”
Section: Introductionunclassified
“…Tem-se verificado que os elementos de maior mobilidade encontram-se, predominantemente, nas formas químicas solúvel, trocável e ligados a carbonato, enquanto os de baixa mobilidade aparecem ligados às frações óxidos de Fe, Mn, além das frações orgânica e residual (Amaral Sobrinho et al, 1994). Apesar das vantagens do processo de extrações sequenciais em relação apenas à determinação dos teores totais de metais pesados no solo, podem ocorrer problemas de baixa seletividade dos extratores (Shan & Chen, 1993;Shiowatana et al, 2001), redistribuição dos metais durante os processos de extração (Tu et al, 1994;Rakasasalaya et al, 1996) e dependência dos resultados das condições operacionais (Sahuquillo et al, 1999 ao ar e passadas em peneira com malha de 2 mm (TFSA). A textura e as características químicas da TFSA (métodos descritos em Embrapa, 1997;Kummer et al, 2010) e a mineralogia da fração argila (métodos apresentados por Melo et al, 2001Melo et al, , 2002Kummer et al, 2010) das amostras são apresentadas nos quadros 2 e 3, respectivamente.…”
Section: Introductionunclassified
“…(Chao et al, 1983). Shiowatana and et al have also reported that increasing the concentration of hydroxylamine in the reducible fraction step from 0.04 to 0.5 mol L À1 affected the extraction efficiency for Fe, Mn and Zn (Shiowatana et al, 2001).…”
Section: Effect Of Concentration Of Nh 2 Oh-hcl On Extraction Efficiencymentioning
confidence: 93%
“…For steps 1 to 3, the extraction was repeated twice. Multiple extractions have been found to give better recovery than single extractions for exchangeable 39 , 40 and oxidisable 33 fractions, hence the inclusion of a second extraction in this protocol. Two extractions were found necessary in step 2 to maintain the end pH at pH 5.…”
Section: Laboratory Analysismentioning
confidence: 99%